2014
DOI: 10.3892/ijo.2014.2813
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of UHRF1 promotes EMT via inducing CXCR4 in human cancer cells

Abstract: Activation of epithelial-mesenchymal transition (EMT) is important for malignant tumor progression exhibiting migratory and invasive properties. UHRF1 (ubiquitin-like, with PHD and RING finger domains 1), as an epigenetic regulator, plays a crucial role in DNA CpG methylation, chromatin remodeling and gene expression. Many studies demonstrated that UHRF1 is aberrantly expressed in various types of human cancer. However, the precise role of UHRF1 in human cancers remains highly controversial. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…To validate our previous report 25 , we investigated whether UHRF1 deficiency is associated with the acquisition of mesenchymal characteristics in hepatocellular carcinoma cells. In this regard, we performed western blot analysis to compare the basal levels of UHRF1 and the mesenchymal marker vimentin in HepG2, Hep3B and Huh7 cells with that in normal human fetal hepatocytes (HFHs).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…To validate our previous report 25 , we investigated whether UHRF1 deficiency is associated with the acquisition of mesenchymal characteristics in hepatocellular carcinoma cells. In this regard, we performed western blot analysis to compare the basal levels of UHRF1 and the mesenchymal marker vimentin in HepG2, Hep3B and Huh7 cells with that in normal human fetal hepatocytes (HFHs).…”
Section: Resultsmentioning
confidence: 74%
“…We previously reported that UHRF1 deficiency upregulates CXCR4, thereby leading to EMT 25 . In this study, we confirmed an increase in the mRNA expression of CXCR4 in UHRF1-deficient HepG2 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study indicated that UHRF1 is overexpressed in a variety of tumor tissues such as gastric cancer, bladder cancer and HCC, and UHRF1 overexpression is negatively correlated with prognosis of HCC patients [2126]. Additionally, the proliferative and invasive abilities of tumor cells were significantly inhibited after UHRF1 knockdown, while opposite results were obtained when UHRF1 was upregulated [2729]. Furthermore, studies have shown that UHRF1 is regulated by microRNAs, and mTOR inhibitors showed an antitumor effect by downregulating UHRF1 [30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…UHRF1 is a well-known epigenetic regulator. Recently, Liu et al [25] demonstrated that UHRF1 promotes EMT via the suppression of retinoblastoma 1 in human osteosarcoma cell lines, while Jung et al [26] reported that the downregulation of UHRF1 promotes EMT through the activation of the CXCR4-signaling pathway in hepatocellular carcinoma, breast cancer, and colon cancer cells. Although the precise role of UHRF1 in the EMT process has not been fully elucidated, recent reports on the UHRF family in epithelial malignant cells support our findings that UHRF2 negatively regulates EMT because of structural similarities between UHRF1 and UHRF2, followed by a potential functional conservation such as the maintenance of DNMT1-mediated DNA methylation [13, 27].…”
Section: Discussionmentioning
confidence: 99%